Distributed voltage and frequency synchronisation control scheme for islanded inverter‐based microgrid. Issue 2 (18th July 2018) - Shrivastava, Sonam; Subudhi, Bidyadhar; Das, Susmita
Abstract : This study presents a fully distributed control paradigm for secondary control of islanded AC microgrid (MG). The proposed method addresses both voltage and frequency restoration for inverter‐based distributed generators (DGs). The MG system has droop controlled DG units with predominantly inductive transmission lines and different communication topologies. The restoration scheme is fully distributed in nature, and the DGs need to communicate with their neighbours using a sparse communication network. The proposed control scheme is efficient to provide quick restoration of the voltage and frequency whilst accurate power‐sharing is achieved despite disturbances. Further, convergence and stability analysis of the proposed control scheme is presented. The proposed algorithm avoids the need for a central controller and complex communication structure thereby reducing the computational burden and the risk of single‐point‐failure. The performance of the proposed control scheme has been verified considering variations in load and communication topologies and link delay by pursuing an extensive simulation study in MATLAB/SimPowerSystem toolbox. The proposed control scheme supports plug‐and‐play demand and scalability of MG network. The proposed control scheme is also compared with the neighbourhood tracking error based distributed control scheme and observed that the former exhibit faster convergence and accurate performance despite disturbances in MG network.